CO2/CH4 adsorption over functionalized multi-walled carbon nanotubes; an experimental study, isotherms analysis, mechanism, and thermodynamics - Mukhtar, A. (Elsevier B.V., 2020)
Understanding of the interactions of the CO2 molecules with pore structure and surface functionalities during natural gas purification provides significant knowledge about potential adsorbent materials. This study reports the oxygen-rich surface functional groups attachment on MWCNTs followed by characterization, low-pressure selective CO2/CH4 adsorption behavior, the impact of temperature, isotherms analysis, mechanism study, thermodynamic behavior, turnover frequency, and turnover number analysis. The FESEM and TEM analysis revealed some negligible defect on MWCNTs surface. The MWCNTs surface roughness was observed after ultra-sonication with the attachment of oxygen functionalities without opening ends of MWCNTs. Structural sustainability and thermal instability were observed due to the early decomposition of (-COOH) groups at < 225 Â°C. Functionalization results BET surface area loss indicating the pore filling by acid molecules with existence of transport pores demonstrating excellent mass transfer characteristics. The functionalities exhibited enhancement in CO2 uptake capacity from 0.0874 to 0.3274 mmol/g. The temperature influences indicated that the adsorption is thermodynamically controlled. CO2/CH4 selectivity reduced at elevated pressure directing the pressure-driven pore-filling mechanism. Isotherms analysis revealed that the low temperature favors high affinity. The separation factor was found less than unity indicating the process favorability. Additionally, isotherms analysis revealed heterogeneity of MWCNTs with multi-layer formation. Furthermore, D-R model fitting showed adsorption energy values within the range of 3.462â8.087 kJ/mol indicating the adsorption is physisorption leading to combination of physisorption and chemisorption at elevated temperatures. Finally, thermodynamic exhibited positive ÎGÂ°, and negative ÎHÂ° and ÎSÂ° attributing the energy requirement for process startup, exothermic, and reduction in the randomness. The TON and TOF values were found to be within the specified range of MWNCTs. Â© 2019 Elsevier Inc.